(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Antilock braking systems (ABS) are utilized as a part of advanced autos to keep the vehicle’s wheels from deadlocking when the brakes are connected. The control performance of ABS utilizing linear and nonlinear controls is cleared up in this research. In order to design the control system of ABS a nonlinear dynamic model of the antilock braking systems is derived relying upon its physical system. The dynamic model contains set of equations valid for simulation and control of the mechanical framework. Two different controllers technique is proposed to control the behaviors of ABS. The first one utilized the PID controller with linearized technique around specific point to control the nonlinear system, while the second one used the nonlinear discrete time controller to control the nonlinear mathematical model directly. This investigation contributes to more additional information for the simulation of the two controllers, and demonstrates a clear and reasonable advantage of the classical PID controller on the nonlinear discrete time controller in control the antilock braking system.